Von Bulgakow bis Loest. ,Im Osten nichts Neues' - Muylaert, Marc (Studia Germanica Posnaniensia, 2018)
Although the work of Bulgakov and the one of Least are widely spaced time, they present a surprising parallel. The preocupation of the two of the authors is the connection of literature to the official authorities which limit the literary production and develop their novelistic fiction from a certain real and practical problem. German and Russian analyse the administrative system in wich the literary creation should be done. The similarity of the systems is perfect and the approach of the authors is identical. They don‘t fundamentally question (as prejudiciable to the idea of freedom) all the structures wich determine the material aspects of their production. Their irony is exerced against their colleagues, mediocre writters but go getters, who invested the system and perverted it in order to ensure the adventages. Bulgakov has superbly come to reject all connection with the system, the creation finally couldn't be possible only in the axetism. When all is scred and done, Loest is strongly apposed to some practises wich are only in favorer of mediocrity and by wich a censure can be express a sweet but effective censure. Perversion is total for hemi where a system, by dint of solicitude ends smolder. But the paradoxe is that the best work from these two authors is due to the confrontation to a system where they denounced the ciseless, indeed even noxiousness for all literary creation.